Multidisciplinary surgical approach in extensive trauma injury of upper extremity - case report - Todorovikj, L; Gramatnikovski, N; Cokleska N; Racaj A; Aleksovski Z; Gjorikj, S (Croatian society for pediatric surgery, 2022)
Polytraumatized 9 year old patient, in a hemorrhagic and traumatic shock with severe laceration injury of the left upper extremity and early sings for acute critical ischemia, was admitted in our emergency department Surgery was initiated within the first hour of hospital admission. Exploration revealed highly contaminated wound, extensive soft tissue damage, severe muscle laceration, axillary artery lesion, thrombosed axillary vein, neuropraxia of the brachial plexus and open humeral shaft fracture grade III according Gustilo- Anderson classification. The axillary artery lesion was replaced with a reversed saphenous vein interposition graft and the axillary vein thrombus was removed using Fogarty catheter. The open humeral shaft fracture was stabilized with external fixation ostheosynthesis. After meticulous and radical injury zone excision was completed, soft tissue coverage and tension free approximation of the muscle and skin was achieved. Pre-and intraoperative broad spectrum antibiotics were used. Postoperative follow up was satisfactory with acceptable functional and aesthetic outcome. Complete healing of the humeral shaft fracture was noticed after 18 weeks. Rehabilitation program was started after humeral fracture was stable. The treatment of this kind of injuries require multidisciplinary surgical approach that includes traumatology surgeons, vascular surgeons and plastic surgeons.